Exploring determinants of shared bicycle usage in Ningbo: an integration of behavioral theories - Nazatul Faizah Haron,; Yin, Shuang; Siti Rahyla Rahmat,; Nadhrah A Kadir,; Shankar Karuppayah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Most consumers favor shared bicycles for their advantages of convenient use, time-saving, cheap price, and green environmental protection, but most issues exposed in the rapid rise of shared bicycles have gradually reduced the willingness of users to continue using them. The objectives of this study are 1) To identify the willingness of respondents to use shared bikes and 2) To discover corresponding solutions to overcome the obstacles to the healthy development of shared bicycles. This research discovered that the development status of shared bicycles in Ningbo is not optimistic, with prominent problems such as disorderly parking of shared bicycles, chaotic deposit management of shared bicycles, and an imperfect supervision system of shared bicycles. Therefore, based on reasoned action theory, technology acceptance model theory, social influence theory, and innovation diffusion theory, eight factors are proposed to affect the willingness to use shared bicycles. Data on consumers' shared bike riding experience and factors affecting consumers' willingness to use shared bikes were collected through questionnaires. Consequently, the relationship between these factors and consumers' willingness to use shared bicycles is explored through binary logistic regression analysis. From the perspective of consumers, summarizing the development status quo and existing problems of shared bicycles in Ningbo City, as well as providing corresponding solutions, is inevitable. The research suggests that user-friendliness, satisfaction, usefulness, social influence, individual innovativeness, corporate image, and time efficiency positively affect consumers' willingness to use shared bicycles. In contrast, cost efficiency does not significantly impact consumers' willingness to use shared bicycles.